Electrical properties of Ba0.9Ca0.1Zr0.1Ti0.9O3 ceramics induced by SFN heterogeneous seed - Intatha U. (2017)
© 2017 Elsevier Ltd and Techna Group S.r.l. The effect of heterogeneous seed crystal on the electrical properties of Ba 0.9 Ca 0.1 Zr 0.1 Ti 0.9 O 3 (BCZT) ceramics was investigated. The SrFe 0.5 Nb 0.5 O 3 (SFN) crystal was used as the heterogeneous seed. The seed was prepared by molten salt method. All ceramic samples showed pure perovskite phase (BCZT: x mol% SFN, x = 0–0.5). The samples at x = 0.0–2.0 showed coexistence between rhombohedral and tetragonal phase, both of which transformed to tetragonal phase at x ≥ 3.0. Density values were in the range of 5.59–5.74 g/cm 3 . The value of dielectric constant (ε r ) at room temperature of SFN seed-added samples was higher than that of the non-seed sample. The highest value of ε r ∼ 10290 was found in SFN seed at 3.0 mol%. The tan δ values tended to decrease when SFN seed content increased and were lower than 0.02 for all samples (1 kHz at room temperature). The lowest value of Ac conductivity (σ ac ) was obtained at the highest SFN seed content. P-E hysteresis loop changed to greatly slim loop with higher SFN seed content. Furthermore, remnant polarization (P r ) and coercive field (E c ) decreased with increasing SFN seed content. In addition, piezoelectric coefficient (d 33 ) and electromechanical coupling coefficient (k t ) presented no significant change with the smaller SFN seed content ranging from x = 0.0 to x = 2.0.